MANAGEMENT OF CHOLEDOCHOLITHIASIS IN PAKISTAN: A COMPARISON OF ENDOSCOPIC RETROGRADE CHOLANGIOPANCREATOGRAPHY AND LAPAROSCOPIC COMMON BILE DUCT EXPLORATION - Amin , I; Munir , A; Memon , ML; Zahra , SH; Cheema , HMKN; Niaz, H (Biological and Clinical Sciences Research Journal, 2023)
The objective of this study was to compare the management outcomes of endoscopic retrograde cholangiopancreatography (ERCP) and laparoscopic common bile duct exploration (LCBDE) for choledocholithiasis in Pakistan, based on a sample size of 150 patients. A retrospective analysis was conducted on 150 patients diagnosed with choledocholithiasis who underwent either ERCP (n=75) or LCBDE (n=75) at a tertiary care hospital in Pakistan. Patient demographics, procedure-related variables, postoperative outcomes, and complications were collected and analyzed. Primary outcome measures included stone clearance rates, procedure-related complications, length of hospital stay, and cost-effectiveness. The study included 150 patients, with 75 in each group. The stone clearance rate was significantly higher in the LCBDE group (82.7%) compared to the ERCP group (68.0%). However, the ERCP group had a lower incidence of procedure-related complications (12.0%) than the LCBDE group (24.0%). The mean length of hospital stay was shorter in the ERCP group (4.2 days) compared to the LCBDE group (6.1 days). Cost analysis revealed that ERCP was more cost-effective than LCBDE. In managing choledocholithiasis, ERCP and LCBDE are effective treatment options in Pakistan. LCBDE demonstrated a higher stone clearance rate (82.7%), while ERCP had a lower incidence of procedure-related complications (12.0%) and a shorter length of hospital stay (4.2 days). In terms of cost-effectiveness, ERCP was found to be more favorable.